2020
DOI: 10.1093/braincomms/fcaa223
|View full text |Cite
|
Sign up to set email alerts
|

Hyperperfusion in the thalamus on arterial spin labelling indicates non-convulsive status epilepticus

Abstract: Non-convulsive status epilepticus describes the syndrome of unexplained impaired consciousness in critically ill patients. Non-convulsive status epilepticus is very likely to lead to delayed diagnosis and poor outcomes because of the absence of convulsive symptoms. EEG is essential for the diagnosis of non-convulsive status epilepticus to establish the association between periodic discharges and rhythmic delta activity in addition to ictal epileptiform discharges according to the Salzburg criteria. Arterial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
0
31
0
1
Order By: Relevance
“…In the first place, no single isolated seizure episode, even accompanied by cortical cerebral hyperperfusion, was associated to increased perfusion in thalamus. Moreover, as reported first on arterial spin labeling sequence on MRI by Ohtomo et al [24] and recently on pCT by Giovannini et al [22], thalamic hyperperfusion, although not sensitive, is highly specific of continuous sustained ictal activity compatible with SE on EEG. Therefore, the present study suggests that early pCT findings, together with other factors, such as clinical presentation [25], could serve as an adjunctive diagnostic tool for NCSE risk stratification; thus, probably avoiding delayed management in acute settings, especially if accompanied by the highly specific feature of thalamic hyperperfusion.…”
Section: Discussionmentioning
confidence: 86%
“…In the first place, no single isolated seizure episode, even accompanied by cortical cerebral hyperperfusion, was associated to increased perfusion in thalamus. Moreover, as reported first on arterial spin labeling sequence on MRI by Ohtomo et al [24] and recently on pCT by Giovannini et al [22], thalamic hyperperfusion, although not sensitive, is highly specific of continuous sustained ictal activity compatible with SE on EEG. Therefore, the present study suggests that early pCT findings, together with other factors, such as clinical presentation [25], could serve as an adjunctive diagnostic tool for NCSE risk stratification; thus, probably avoiding delayed management in acute settings, especially if accompanied by the highly specific feature of thalamic hyperperfusion.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent study of 28 NCSE patients, thalamic hyperperfusion were confirmed in 57% of cases and showed particularly high accuracy in diagnosing NCSE 12 . In the same study, cortical hyperperfusion was observed in 86%.…”
Section: Discussionmentioning
confidence: 91%
“…In comparison with self-limiting seizures, ASL showed a modest degree of specificity (58.7%) for SE. Additionally in some clinical practice such as NCSE or subtle SE, MRI might be taken before EEG, and abnormal findings in MRI can lead to more immediate management taking advantage of high sensitivity of ASL, which can help shorten the time to EEG or administer anti-epileptic drugs 12 . Considering the poor prognosis of refractory SE, appropriate and timely treatment can help improve the prognosis and reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations